Compton scattering of polarized electron beam - Drebot, I.; Karnaukhov, I.; Zelinsky, A. (Вопросы атомной науки и техники, 2004)
Compton scattering of polarized photon beam by polarized relativistic electron beam is considered in the report.
The numerical comparison of Compton scattering intensity and polarization intensity has been carried out for different directions of initial photon and electron polarization. It was shown that the use of polarized beam leads to considerable increasing of Compton scattering intensity in the range of high photon energy for initial electron beam energy beginning from 5 GeV. The effect of initial polarization of photon and electron beams to final polarization of
scattered photon beam was considered. Розглянуто комптонівське розсіяння фотонного пучка на поляризованому релятивістському електроні. Розглянуто
диференційний перетин комптонівського розсіяння з урахуванням ефектів поляризації. Доведено, що застосування
поляризованих пучків призводить до значного зросту спектральної інтенсивності фотонів, в області високих енергій для
початкової енергії електронного пучка від 5 ГеВ. Розглянуто вплив поляризації початкових фотонів на поляризацію
комптонівських фотонів. Рассматривается комптоновское рассеяние поляризованного фотонного пучка на поляризованном релятивистском
электроне. Рассмотрено дифференциальное сечение комптоновского рассеяния с учетом эффектов поляризации. Было
сделано сравнение для различных поляризаций. Показано, что применение поляризованных пучков приводит к значительному увеличению спектральной интенсивности фотонов, в области высоких энергий, для начальной энергии электронного пучка от 5 ГэВ. Рассмотрено влияние поляризации начальных фотонов на поляризацию комптоновских фотонов.